Attentional vigilance of food information in disordered eating behaviors - Jin, Luyao; Han, Wenyue; Zheng, Zheng (Frontiers in Psychiatry, 2023)
Introduction Disordered eating behaviors (DEBs) are very common among female college students, which seriously endanger their health and well-being. Therefore, the study of the mechanism of DEBs can provide effective evidence for early detection and intervention. Methods In total of 54 female college students were recruited and assigned to DEB group (n = 29) and healthy control (HC) group (n = 25) according to their scores in the Eating Attitudes Test-26 (EAT-26). Then, the Exogenous Cueing Task (ECT) was used to evaluate their reaction time (RT) to the location of a target dot preceded by a food or neutral cue. Results The study found that compared with HC group, DEB group showed more attentional engagement to food stimuli, indicating that attentional vigilance to food information could be considered as a specific attentional bias of DEBs. Discussion Our findings not only provide evidence of the potential mechanism of DEBs from the perspective of attentional bias, but also can be considered as an effective and objective indicator for early screening of subclinical eating disorders (EDs).